Responding to SARS-CoV-2 in South Africa: what can we learn from drug-resistant tuberculosis?. Issue 1 (23rd July 2020) - Ndjeka, Norbert; Conradie, Francesca; Meintjes, Graeme; Reuter, Anja; Hughes, Jennifer; Padanilam, Xavier; Ismail, Nazir; Kock, Yulene; Master, Iqbal; Romero, Rodolfo; te Riele, Julian; Enwerem, Martin; et al.
The novel coronavirus strain, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was first reported from China in December 2019 [1]. As of 14 May, 2020, more than 4.4 million individuals have tested positive for SARS-COV-2 globally [2]. More than 300 000 individuals have died globally due to SARS-COV-2 [2]. In South Africa, cumulatively at the same time point, 12 739 individuals have been infected and 238 deaths reported [2]. Tuberculosis (TB) is the leading infectious disease cause of death with 1.4 million deaths in 2018 [3]. Drug-resistant tuberculosis (DR-TB) is a threat to TB control globally. Over the past decade, several interventions have improved the outcomes of DR-TB patients and reduced the burden of disease. We discuss lessons from DR-TB interventions in South Africa that could be helpful in the fight against SARS-COV-2. Rapid adoption of new diagnostic tools, parallel process of research and implementation, decentralisation of services, the use of personal protective equipment, as well as strong partnership and collaboration, could strengthen the fight against COVID-19 https://bit.ly/2XupDNe